Morphology, accumulation and survival of Desmanthus under different planting densities and harvest heights. (11th October 2022) - Medeiros, Aurielle S.; dos Santos, Mércia V. F.; da Cunha, Márcio V.; de Mello, Alexandre C. L.; Simões Neto, Djalma E.; de Oliveira, Osniel F.; Muir, James P.; Dubeux, Jose C. B.; dos Santos, André E.
Abstract: The use of legumes is an important strategy for animal feeding, especially during the dry season. The aim was to evaluate the effect of planting densities (40, 000; 15, 625 and 10, 000 plants ha −1 ) and harvest heights (20 and 40 cm) on the morphology, accumulation and survival of Desmanthus ( Desmanthus pernambucanus [L.] Thellung), cultivated in subhumid tropical region, as well as to estimate the repeatability of the evaluated characteristics and the optimal number of measurements. The treatments were randomized in blocks, with subdivided plots and four replicates. Planting densities were evaluated in the plots and the harvest heights in the subplots. Eight harvests were carried out with an interval of 84 days. Morphological and productive characteristics and survival were evaluated. Cultivation under density of 40, 000 plants ha −1 produced taller plants, with higher leaf area index (LAI = 0.98), light interception (LI = 49%), individual accumulations (18.8 g DM plant −1 ) and by area (576.5 kg DM ha −1 harvest −1 ), although resulting in reduced plant stand (66%). Harvest heights do not affect accumulation and survival. It is possible to reduce the number of measurements for stem diameter, number of leaflets per leaf ( R 2 = 95%), plant height, canopy diameter, LAI, LI, leaf length and width, number of leaves per branch, branch diameter and LBR ( R 2 = 90%), optimizing resources for future research. Desmanthus has potential for use in protein banks, being harvested in the rainy season, conserved and supplied in addition to animals, but plant growth is minimal during the dry season under rainfed conditions.